Criminogenic and harm-enabling features of social media platforms: The case of sharenting practices - Lavorgna, Anita (European journal of criminology, 2023)
Sharenting ? that is, the sharing of identifying and sensitive information of minors, who are often overexposed online by parents or guardians ? has, at times, criminogenic potential, as the information shared can enable both heinous crimes and other types of harmful conduct. Whilst most research on sharenting has focused on the sharenters and their agency, there is a gap in addressing whether and to what extent social media platforms display criminogenic or other harm-enabling features that can render sharenting risky for affected minors. By relying on an adapted crime proofing of legislation approach, our contribution analyses the self-regulations (in the form of corporate documents and forms of self-organisation) of five major social media platforms and identifies several risks and vulnerabilities to harmful sharenting practices embedded in the platforms? policies. In doing so, the study demonstrates how criminological imagination can effectively contribute to the multidisciplinary debates on digital ecosystems and their regulation, paving the way for a reduction of criminogenic and harmful opportunities online.